Corporate social responsibility in emerging economies: Investigating firm behavior in the Indian context. (21st August 2018) - Panda, Swati; D'Souza, Derrick E.; Blankson, Charles
Abstract : Scholars have questioned the appropriateness of using a western‐centric framework to investigate corporate social responsibility (CSR) in emerging economies. This study assesses the appropriateness of using such a framework in one emerging economy—India. More specifically, the drivers of CSR and their impact on firm‐level CSR activity in the Indian context are investigated and compared with those in developed economies. Content analysis of 369 CSR policy statements of publicly traded Indian firms revealed the factors that drive CSR activities of Indian firms are similar to those found in developed economies. However, the ways firms respond to the drivers of CSR are surprisingly different in the Indian context, and these differences can be traced to attributes of the Indian socio‐cultural context. Implications and recommendations for future research conducted in India, and in other emerging economies, are offered.